Technology of fuel creation on the basis of waste fuel energy sources - Борук, Сергій Дмитрович (Technology audit and production reserves, 2014)
The direction for reducing anthropogenic impact of the fuel industry enterprises on the environment by creating combination fuel, based on their solid and liquid waste was investigated in the paper. Using modern physico-chemical research methods - gravimetric, rheological, optical, sedimentation, calorimetric and electrophoretic and statistical analysis of the results revealed an optimal carbon slurry fuel composition, which provides saving the necessary physical and chemical properties under almost complete fuel component burn-up, and minimal pollutants emission in the environment. The possibility of using liquid pyrolysis products of polymer waste as a dispersion medium for obtaining highly concentrated coal slurries is shown. The technological mode for obtaining coal slurry fuel, based on waste "T" coal and brown coal is proposed. The economic and environmental feasibility of such systems as an energy source is shown. Creating highly concentrated coal slurries, based on liquid pyrolysis products of rubber allows an effective use of low-calorie energy sources. Fuel with the developed composition can be recommended for introducing at power generation enterprises. Their use will allow to reduce the imported fuels consumption, improve the ecological situation in many regions of Ukraine.